To What Extent is The Rhetoric and Reality of The Big Society Agenda Aligned To Encourage Local Social Entrepreneurial Activity in the UK? - Vyas, Rupali (2012)
This paper’s objective is to focus on the emergence and evolution of social enterprise organisations in the UK and the increasing role they are expected to play in the UK’s Coalition government’s Big Society agenda. Due to the scope of the assignment, the paper is limited in its discussion but will specifically investigate the extent to which the rhetoric and reality of the big society agenda are aligned to encourage social entrepreneurial activity in the UK. It will consider the following: 1. The economic logic of the state to implement such measures 2. Institutional legitimacy of social enterprises The paper takes into account the socio-political context of the country and general ‘mood’ of the economy in order to gain a broader understanding of why the popularity of social entrepreneurial activity is growing. The paper aims also aims to investigate discourses that influence the role of social enterprise in delivering services and specifically try to understand how social enterprises innovate to respond to the environment by providing market-based solutions and businesslike models to ‘add value’ to civic society and decrease inequality. In taking a balanced approach, the paper will also be assessing the extent to which social enterprises are challenged as whilst attempting to increase their social contribution, are restricted due to the complex web of policies, bureaucracies and contradictions that exists.